2021
DOI: 10.1186/s40100-021-00188-2
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption patterns, nutrient adequacy, and the food systems in Nigeria

Abstract: Previous studies in Nigeria examined food and nutrition security mainly using anthropometric indicators, total calorie intake, or the household dietary diversity score (HDDS). However, recent evidence on nutrient and dietary gaps, especially from nationally representative surveys, is weak. This study contributes by examining factors influencing household mean nutrient adequacy and HDDS with focus on components of food systems in Nigeria. Based on the 2015/16 Nigeria General Household Survey, we found that frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
(30 reference statements)
2
17
0
1
Order By: Relevance
“…Studies have used the AME with Household Consumption and Expenditures Surveys data and found values were comparable to individual 24-h recall intake data (24) . However, since target groups in nutritional programmes are usually not the adult men but women of reproductive age, as they are among the most vulnerable groups and thus a highly relevant group of interest to include in research, the Adult Female Equivalent (AFE) referring to an adult non-pregnant non-lactating woman, 20-30 years, was used as suggested previously (27) . In the present study, we followed the AFE strategy to transform household food consumption into intake of a reference individual (24) , with a correction based on the recommendations of the Human Energy Requirements (28) for all individuals in the households, considering their age and gender.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Studies have used the AME with Household Consumption and Expenditures Surveys data and found values were comparable to individual 24-h recall intake data (24) . However, since target groups in nutritional programmes are usually not the adult men but women of reproductive age, as they are among the most vulnerable groups and thus a highly relevant group of interest to include in research, the Adult Female Equivalent (AFE) referring to an adult non-pregnant non-lactating woman, 20-30 years, was used as suggested previously (27) . In the present study, we followed the AFE strategy to transform household food consumption into intake of a reference individual (24) , with a correction based on the recommendations of the Human Energy Requirements (28) for all individuals in the households, considering their age and gender.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Improved diet is believed to have a multiplier effect transversely to the Sustainable Development Goals (SDGs) [ 1 ]. The Food Consumption Score (FCS), a food frequency indicator developed by the World Food Programme (WFP) that intends to capture both diet quantity and quality of household food consumption [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, previous studies examined food consumption patterns and certain aspects of food security and nutrition (e.g., Babatunde and Qaim, 2010;Akerele, 2015;Akerele et al, 2017;Ecker and Hatzenbuehler, 2021;Mekonnen et al, 2021). According to Ecker and Hatzenbuehler (2021), there has been no general trend toward a transition into the consumption of more nutritious foods, despite increased availability of per capita calories at national level over the previous three decades in Nigeria.…”
Section: Introductionmentioning
confidence: 99%